Bimbingan Karir dalam Menumbuhkan Motivasi Entrepreneurship Peserta Didik - Bili Hakiki Jenawi (Department of Islamic Guidance and Counseling, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2018)
This paper aims to find out how the process, the program and the results of career guidance in fostering motivation Entrepreneurship learners in JampangKulonSukabumi. This research method using direct method through two way discussion from supervisor to learners and from learners to mentors, then also through lecture, observation method observed directly with the parties of high learning, consultation method that is after observation learners are given the opportunity to consult directly with the parties from the college. The results of this study show the implementation of career guidance in Vocational High School Al-Mubarokatusaa'adillah indirectly has been practicing career guidance activities to the learners. Each type of career guidance is also able to inspire and encourage the learners to remain confident that they can enter various types of work world even though they do not have much expertise. Because with the guidance of this career of course the learners will be ready when continuing life in the community, as for the indicator Entrepreneurship: a) Innovative means to introduce a new, b) Creative which means have the ability to create or produce something new, and c ) Productive which means willingness to produce something or a lot to bring something result from work. Penelitian ini bertujuan untuk mengetahui bagaimana proses, program dan hasil dari bimbingan karir dalam menumbuhkan motivasi Entrepreneurship peserta didik di Jampang Kulon Sukabumi. Metode penelitian ini menggunakan metode direct (metode langsung) melalui diskusi bersama dua arah dari pembimbing kepada peserta didik dan dari peserta didik kepada pembimbing, kemudian pula melalui ceramah, metode observasi mengamati secara langsung dengan pihak-pihak peguruan tinggi, metode konsultasi yakni setelah melakukan observasi peserta didik diberikan kesempatan berkonsultasi langsung dengan pihak-pihak dari perguruan tinggi. Hasil penelitian ini menunjukan pelaksanaan bimbingan karirdi Sekolah Menengah Kejuruan Al-Mubarokatusaa’adillah secara tidak langsung telah mempraktikkan kegiatan bimbingan karir kepada para peserta didik. Setiap jenis bimbingan karirnya juga mampu menginspirasi dan memberi semangat kepada para peserta didik untuk tetap percaya diri bahwa mereka bisa memasuki berbagai jenis dunia kerja meskipun tidak mempunyai banyak keahlian. Karena dengan adanya bimbingan karir ini tentu para peserta didik akan siap ketika melanjutkan kehidupan di dalam bermasyarakat, adapun indikator Entrepreneurshipnya : a) Inovatif yang artinya memperkenalkan suatu yang baru, b) Kreatif yang artinya memiliki kemampuan untuk menciptakan atau menghasilkan sesuatu yang baru, dan c) Produktif yang berarti kemauan untuk menghasilkan sesuatu atau banyak mendatangkan sesuatu hasil dari berkarya.